Integration of Multifunctionality in a Colloidal Self‐Repairing Catalyst for Alkaline Water Electrolysis to Achieve High Activity and Durability - Yoshiyuki Kuroda; Daiji Mizukoshi; Vinay Yadav; Tatsuya Taniguchi; Yuta Sasaki; Yoshinori Nishiki; Zaenal Awaludin; Akihiro Kato; Shigenori Mitsushima (Advanced Energy & Sustainability Research)
Self‐repairing catalysts are useful for achieving alkaline water electrolyzers with long lifetimes under intermittent operation. However, rational methodologies for designing self‐repairing catalysts have not yet been established. Herein, hybrid cobalt hydroxide nanosheets (Co‐ns), with a high deposition (repairing) rate, and β‐FeOOH nanorods (Fe‐nr), with high oxygen evolution reaction (OER) ability, are electrostatically self‐assembled into composite catalysts. This strategy is developed to integrate multifunctionality in self‐repairing catalysts. Positively charged Co‐ns and negatively charged Fe‐nr form uniform composites when dispersed in an electrolyte. These composites are electrochemically deposited on a nickel electrode by electrolysis at 800 mA cm−2. Co‐ns form a conductive mesoporous assembly of CoOOH nanosheets as a support. Fe‐nr are then distributed on the CoOOH nanosheets as active sites for the OER. Because of the high deposition rate of Co‐ns, the amount of Fe‐nr deposited increases 22 times compared to when Fe‐nr is deposited alone, and the OER current density increases 14 times compared to that of Co‐ns alone. The composite self‐repair catalyst shows the highest activity and durability under an accelerated durability test (ADT), and its degradation rate decreases from 84 μV cycle−1 (Fe‐nr only) to 60 μV cycle−1 (composite catalyst) under ADT conditions without repair.